Koora kahan daaloon - Ghazala, Nomani; Bani, Abedi (book group Karachi, 2017)
Koora Kahan Daaloon (Where Should I Throw the Trash?) is likely a children's book that teaches the importance of waste management and cleanliness. It might explain the concept of garbage disposal, recycling, and the harmful effects of littering.